2019
DOI: 10.1097/cm9.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance and pathogenic spectrum of patients coinfected with nontuberculous mycobacteria and human-immunodeficiency virus in Chengdu, China

Abstract: Background: Human-immunodeficiency virus (HIV) infection is increasing worldwide and nontuberculous mycobacteria (NTM) is an established microbiologic cause of pulmonary disease, lymphadenitis, and disseminated disease in cases of advanced immune suppression. Data on patients coinfected with HIV and NTM are limited. Thus, this study aimed to analyze the clinical characteristics, drug resistance, and pathogen spectrum of patients coinfected with both HIV and NTM in the Chengdu area of China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
(11 reference statements)
2
8
1
1
Order By: Relevance
“…Our findings are consistent with previous studies indicating a high resistance rate to first-line anti-tuberculosis drugs in the NTM [70,71]. However, the resistance rates of ethambutol and rifampicin were relatively lower than that of isoniazid, which disagrees with a previous study [72].…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are consistent with previous studies indicating a high resistance rate to first-line anti-tuberculosis drugs in the NTM [70,71]. However, the resistance rates of ethambutol and rifampicin were relatively lower than that of isoniazid, which disagrees with a previous study [72].…”
Section: Discussionsupporting
confidence: 83%
“…In Chengdu, MAC and M. kansasii are dominant in patients with HIV/AIDS [26], consistent with the prevalence of NTM strains in Chongqing. A meta-analysis of NTM prevalence in mainland China [27] has shown that M. abscessus and M. avium are the main epidemic strains in Guangdong, consistent with the findings in Chongqing, whereas M. intracellulare and M. avium are the main epidemic strains in Beijing, Zhejiang, and Jiangsu.…”
Section: Discussionsupporting
confidence: 67%
“…To diagnose disseminated NTM infection, one or more isolates from blood, cerebrospinal fluid, bone marrow, pericardial, or peritoneal fluid is needed. They often show severe drug resistance in HIV-positive patients: a Chinese study demonstrated 100% isoniazid resistance, and 94.9% rifampicin and streptomycin resistance, with a relatively lower number of unresponsive infections treated with ethambutol (52.5%) and clarithromycin (33.9%) [31].…”
Section: Disseminated Ntm Infectionsmentioning
confidence: 99%